Transitions in writing - Spelman Miller, Kristyan; Stevenson, Marie, 1961- (Studies in writing, 2018)
Transitions in Writing addresses the experiences of writers as they move between contexts of writing and juggle new and different demands. Spelman Miller and Stevenson bring together research by scholars in a range of settings across the world who approach transition from different standpoints. Transition is often conceived of as a change in setting, coinciding with physical or temporal relocation, such as between stages of an educational or professional career. However, writers also manage more local, micro-level transitions as they move between genres, registers and rhetorical moves to meet the demands of the task. The combination of both macro- and micro-level perspectives on transition offers a novel, broad conception of the types of change a writer encounters, and illustrates a range of methodological approaches appropriate to exploring such transitions.